Lei nº 13.415/2017: implicações no ensino médio integrado na rede de ensino pública do estado do Maranhão - ALENCAR, Nilia Feitosa de (2020)
The research analyzes the policy of integrating High School and Professional Education in the context of Law nº. 13.415/2017. It is linked to the line of research: History, Educational Policies, Work and Human Training, of the Postgraduate Program in Education, at the Federal University of Maranhão. It‘s configured as a research with a qualitative approach, based on the following question: "What are the repercussions of Law nº. 13.415/2017 on the proposal for Integrated High School developed in the State of Maranhão?". In general, it analyzes the repercussions of the current high school reform on EMI. Specifically, we seek to understand the intentions of Law nº 13.415/2017 and analyze the EMI configuration in the Maranhão education network in the context of this legislation. For its development, we used bibliographical, documentary and empirical research as methodological procedures. The bibliographical research included the contribution of theorists such as Marx (2008), Gramsci (2004), Mészáros (2002), Saviani (2019), Silveira (2010), Kuenzer (2003), Ramos (2018), Frigotto (2017), Ciavatta (2011), Moura (2015), Ferreti (2018), Cardozo, Lima (2018), among other scholars on the subject. Through documentary research, the main legal documents related to integrated high school (Decree nº 5.154 / 2004, Basic Document of Integrated High School, DCNs / 2012) and the current reform of high school (Law nº 13.415 / 2017, BNCC / 2018 and DCNs / 2018). The field research had the collaboration of administrative technicians (pedagogues) and coordinators who work with Integrated High School in the Federal Institute of Education, Science and Technology of Maranhão (IFMA), in the State Institute of Education, Science and Technology of Maranhão (IEMA), in the Maranhão's Secretary of Education (SEDUC) and in the University College/UFMA (COLUN). The survey results indicate that, by the end of 2019, none of the three institutions investigated (IEMA, IFMA, COLUN) had joined the current reform of high school. The research allowed to conclude that, although the full units of IEMA have not yet adhered to the current reform, the similarities between their educational model and the proposal of the New High School indicate in the direction of a future adherence to Law nº.13.415. Finally, we emphasize the need for the development of new research seeking to build alternatives of resistance to the implementation of ‗New High School‘.